The impact of climate change on flood resilience strategies in communities of Ringim, Jigawa State, Nigeria - Danraka, Musa Mustapha; Mohamad, Sapura; Ismail, Siti Nur Hannah (UiTM Press, 2025)
The increasing frequency and intensity of climate change-related events, such as floods, present pressing challenges to community resilience worldwide. This qualitative study investigates flood resilience strategies for community resilience in combating climate change at Ringim, Jigawa State, Nigeria. Against the backdrop of global climate change trends, this research explores how residents perceive, believe, and practice flood resilience in the face of evolving climate patterns. Through in-depth interviews, a Focus Group Discussion (FGD) and document analysis, this study examines the complex interactions between changing climatic conditions and community resilience efforts in Ringim. Findings point to the critical need for adaptive measures to enhance flood resilience in light of growing climate risks. By emphasising community participation in crafting sustainable resilience strategies, the research sheds light on the lived experiences and perspectives of Ringim residents. This study proposes areas for further research, including examining the long-term efficacy of adaptive measures, evaluating the impact of community engagement on resilience outcomes, and assessing the influence of governmental policies on building climateresilient communities.